ISOLATION AND CHARACTERIZATION OF LACTID ACID BACTERIA IN CINCALOK REBON SHRIMP (Acetes eryhraeus) MADE USING THE METHOD BACKSLOPPING - Yumna Ramadani; Tjipto Leksono; Dian Iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract               The purpose of this study was to obtain isolates of lactic acid bacteria from cincalo, and to determine the craracteristics of lactic acid bacteria contained in the fermentd cincalok product. The benefit of this research is to provide informatin regarding the isolation and characterization of lactic acid bacteria from cincalok rebon shrimp. The method used in this research is descriptive, namely isolating and characterizing lactic acid bacteria in cincalok fermented products. The concentration of the culture substrate was C0% treatment with 0g culture substrate, C10% with 25g culture substrate, C15% with 37,5g culture substrate, C20% with 50g culture substrate. The parameters observed in this study were PH value, BAL isolation, morphological test (gram stain and motility test), physiological trait test (proteolytic activity test), sensory tes (appearance, texture,,aroma, and taste). The results of this study were obtained PH values with an avarage of 4.53, 4.17. 4.03. and 3.87. and from the isolation carried out, it was obtained 7 bacterial isolates isolated from the fermentation of rebon shrimp cincalok with the backslopping method. In testing the morphological properties of rebon shrimp, gram positive was found, hile in the motility test the seven isolates were non-motile. The proteolityc test on rebon shrim cincalok showed the formation of aclear zone that occurred in the isolates. Sensory test results with the C20 treatment with a visual value of 7.77, a texture value of 7.67, an aroma value of 8.03, and a taste value of 7.20. it can be seen that the C20 treatment was more acceptable to the panelis with the criteria of attaractive appearance, neutral pink color, fresh sour and salty taste of fermented cincalok, and very dense texture, slightly chewy.Keywords: Keywords: Substrat, BAL, Cincalok, Isolation